SLOW INFUSIONS OF GENTAMICIN ARE ASSOCIATED WITH HIGH VARIABILITY IN PEAK GENTAMICIN CONCENTRATIONS IN LOW GESTATION AGE (GA) NEONATES. Issue 1 (14th December 2015) - Medlicott, Natalie; Thomas, Louise; Broadbent, Roland; Reith, David
Abstract : Introduction: Delayed gentamicin delivery through intravenous lines has been reported.Delay is expected to be greater in smaller neonates when the flow rate of carrier intravenous fluid and dose volumes are low. Aim: To investigate the effects of neonate GA and weight on gentamicin peak concentrations after 30 minute infusion or bolus administrations. Methods: Neonates admitted to Dunedin Neonatal Intensive Care Unit in 2008 and 2010 who received gentamicin (2008: 30 minute infusion; 2010: slow bolus) in the first three days of life were included. Peak concentrations were compared and correlations between concentration and weight were investigated over GA bands. Results: There were 151 neonates in 2010 and 118 neonates in 2008. Median (range) GA was 38 weeks (24–42) in 2010 and 34.7 weeks (23.4–42.1) in 2008. Median (range) weight was 3.25kg (0.51–5.65) in 2010 and 2.67kg (0.49–5.11) in 2008. Peak gentamicin concentrations (mg/L) were 8.15±0.098 (at 1.2±0.32h) in 2010 and 9.92±0.17 (at 1.34±0.4h) in 2008. A test for equal variances showed peak concentrations were more variable in 2008 (p0.05). Conclusions: Peak concentrations were more variable following 30 minute infusions and were positively correlated with GA or weight for neonates with GA.